2021
DOI: 10.1242/jeb.230797
|View full text |Cite
|
Sign up to set email alerts
|

Responses of terrestrial polar arthropods to high and increasing temperatures

Abstract: Terrestrial arthropods in the Arctic and Antarctic are exposed to extreme and variable temperatures, and climate change is predicted to be especially pronounced in these regions. Available ecophysiological studies on terrestrial ectotherms from the Arctic and Antarctic typically focus on the ability of species to tolerate the extreme low temperatures that can occur in these regions, whereas studies investigating species plasticity and the importance of evolutionary adaptation to periodically high and increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 119 publications
(151 reference statements)
0
12
0
Order By: Relevance
“…In our study, we showed a linear relationship between ambient microhabitat temperature and measures of both cold and heat tolerance of field-collected specimens of N. groenlandicus . Given the temperatures observed in the field during summer in Narsarsuaq includes subzero night temperatures and peak day temperatures above 40°C ( Sørensen et al, 2019 ; Bahrndorff et al, 2021b ) we advocate that the ability to withstand and remain active at high temperatures and recover fast from low temperature coma is ecologically important, especially for a univoltine species such as N. groenlandicus . This allows the species to, e.g., forage and mate in a transient environment and short summer season.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…In our study, we showed a linear relationship between ambient microhabitat temperature and measures of both cold and heat tolerance of field-collected specimens of N. groenlandicus . Given the temperatures observed in the field during summer in Narsarsuaq includes subzero night temperatures and peak day temperatures above 40°C ( Sørensen et al, 2019 ; Bahrndorff et al, 2021b ) we advocate that the ability to withstand and remain active at high temperatures and recover fast from low temperature coma is ecologically important, especially for a univoltine species such as N. groenlandicus . This allows the species to, e.g., forage and mate in a transient environment and short summer season.…”
Section: Discussionmentioning
confidence: 98%
“…The field work was conducted in July–August 2018 in Narsarsuaq (Southern Greenland, 61.160°N, 45.424°W). This region is characterized by cool temperatures, long winters and short and thermally variable summers ( Böcher and Nachman, 2001 ; Bahrndorff et al, 2021b ). The study site was a heath-like, grass-covered area, where adult N. groenlandicus were collected from the grasses using a sweep net ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations